2018
DOI: 10.2991/itmr.7.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The My Health Record (MyHR) Adoption in General Practices: Literature Review and Future Research Direction

Abstract: Digital health has significant potential in health and healthcare system improvement. My Health Record (MyHR), one of digital health solutions, has been one of the focus in Australia for past few years. Aiming to initiate a study of MyHR adoption in general practices, this paper brings up results of systematically reviewed literature. Four phased tool supported approach was employed and thematic analysis was conducted to describe the findings of the review. Three main themes were identified, focusing on MyHR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Khan et al [17] studied Australia's My Health Record (MyHR), a fully digitized healthcare program, by examining the design of the overall system, its performance, and successes and failure points; and found that healthcare providers were slow to adopt the system, as they failed to recognize the personal benefits of the MyHR system to providers. The usability of the system for multiple users, including doctors, pharmacists, insurance providers etc., had not been highlighted enough during program implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [17] studied Australia's My Health Record (MyHR), a fully digitized healthcare program, by examining the design of the overall system, its performance, and successes and failure points; and found that healthcare providers were slow to adopt the system, as they failed to recognize the personal benefits of the MyHR system to providers. The usability of the system for multiple users, including doctors, pharmacists, insurance providers etc., had not been highlighted enough during program implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Citizens are empowered to log in to a personal web space to book appointments, renew prescriptions, review medication records and health data and communicate with healthcare authorities. Clinicians are able to obtain records from hospitals, laboratory results and data from electronic patient records (Khan et al 2018).…”
mentioning
confidence: 99%
“…Patient portals ideally should be designed with the goal of optimizing patients' ability to help themselves. The combined experience of countries that have implemented patient portals demonstrates the critical need for clinical engagement about health record content and standards (Khan et al 2018). Much of the value that patients derived from the use of portals will be directly affected by the attitudes and actions of physicians, nurse practitioners, nurses and pharmacists (Shah and Liebovitz 2017).…”
mentioning
confidence: 99%